Hubungan Antara Informasi Dan Sikap WUS (Wanita Usia Subur) Dengan Keikutsertaan Pemeriksaan IVA Di Desa Gunungan Wilayah Kerja Puskesmas Kartoharjo Magetan: Hubungan Antara Informasi Dan Sikap WUS (Wanita Usia Subur) Dengan Keikutsertaan Pemeriksaan IVA Di Desa Gunungan Wilayah Kerja Puskesmas Kartoharjo Magetan - Hesty Nur Hasanah (Gema Bidan Indonesia, 2021)
Cervical cancer ranks first, which affects many women in Indonesia. According to WHO about 240,000 cases of female deaths, 80% of cases occur in developing countries. According to data from the Magetan District Health Office in 2017 the IVA examination results, namely (5.79%) were still below the target (30%). Kartoharjo Health Center is a Puskesmas with the lowest IVA examination in 2017, which is equal to (1.01%). The purpose of this study was to find out information and attitudes of WUS with the participation of IVA examinations in Gunungan Village, the working area of Kartoharjo Magetan Health Center. This study is using a cross sectional design. The study sample was 150 women of childbearing age (WUS), using simple random sampling techniques. The independent variable in this study is information and attitude, while the dependent variable in this study is the participation of IVA examination. Data analysis using Chi Square test (α <0.05). The results showed that most of the WUS who had received information had conducted IVA examinations. WUS, which has a positive attitude, has already conducted IVA examinations. Information IVA with the participation of IVA examination obtained Chi Square test results with a p value of 0.00. While the WUS attitude towards the participation of IVA examination was obtained by Chi Square test with a p value of 0.00. There is a relationship between the information and the participation of the IVA examination and there is a relationship between the attitude of WUS and the participation of examination IVA.